Microstructural stability of spark-plasma-sintered Wf/W composite with zirconia interface coating under high-heat-flux hydrogen beam irradiation. (December 2017) - de Lama, M. Avello; Balden, M.; Greuner, H.; Höschen, T.; Matejicek, J.; You, J.H.
Highlights: High-heat-flux loading performance of W fibre-reinforced W composite was investigated. Microstructural damage and chemical impact by plasma loads up to 20 MW/m² was examined. Feasibility of spark-plasma-sintering method for fabricating the composites was studied. Quality of two different specimens produced at different sintering temperatures was compared. It was demonstrated that the composite produced by SPS is applicable to divertor target armour. Abstract: Tungsten is considered as the most suitable material for the plasma-facing armour of future fusion reactors. However, in spite of many advantageous properties, pure tungsten has a major drawback, namely, brittleness at lower temperatures and embrittlement by neutron irradiation. Tungsten fibre-reinforced tungsten (Wf /W) composites are thought to be a promising candidate material for armour owing to the pseudo-toughness effect which is based on controlled cracking of coated interfaces. In this material concept, the reliability of the material during service relies on the fabrication quality as well as the stability of microstructure, particularly, of the interfacial coating under high-heat-flux loads. In this paper, the durability and chemical stability of Wf /W composite specimens under cyclic heat-flux loads up to 20 MW/m² (surface temperature: 1260 °C) was investigated using hydrogen neutral beam. The bulk material was fabricated by means of spark-plasma-sintering (SPS) method using fine tungsten powder and a stack of tungsten wire meshes as reinforcement where the surface of the wire was coated with zirconia thin film to produce an engineered interface. The impact of plasma beam irradiation on microstructure was examined for two kinds of specimens produced at different sintering temperatures, 1400 °C and 1700 °C. Results of microscopic (SEM) and chemical (EDX) analysis are presented comparing the microstructure and element distribution maps obtained before and after heat flux loading. Effects of different sintering temperatures on damage behaviour are discussed. The present composite materials are shown to be applicable as plasma-facing material for high-heat-flux components.